Implementing a Loyalty Card for smartphones using a Bitcoin Like Approach - Costa, Sérgio Manuel Rodrigues da (2014)
Cryptographic currencies have been thriving in the last 5 years, specially since the appearance of Bitcoin in 2009. Factors, as the particular advantages of this type of currency, the current economy conjecture and the evolution of technology are fuelling their popularity. In some countries, cryptographic currency systems are considered to be feasible alternatives to real money by the government and Bitcoin is actually being used in transactions worldwide. The success of Bitcoin is mostly due to its elegant mathematical description, proven security under its assumptions, its decentralized character and anonymity assurance. Apart from the initial effort to securely and correctly implement the system and of the maintenance of the applications, Bitcoin works automatically with the contribution of the nodes of a fully decentralized infrastructure. The full specification of the protocol is readily available, e.g., in the Internet, and it can be used by anyone. This masters programme explored the possibility to use it, with modifications, as a means to implement a system for electronic loyalty cards. In order to do so, the aforementioned cryptographic currency was studied in detail, a set of requirements for the new system and modifications to the original protocol were specified, and a software system was engineered and implemented in the Java programming language. The specification of the modifications was performed while taking the particular application scenario into account. The restrictions deriving from the application scenario were mostly dominated by the fact that the underlying Peer-to-Peer (P2P) infrastructure was to be constituted by smartphones only. The most visible outcome of this masters programme is the fully working prototype of the loyalty card system, comprised by an application for mobile devices and by a server side application. This prototype implements part of the Bitcoin from scratch, starting from the seminal work that defines it, along with the modifications that introduce a central agent for better controlling the quantity of currency per client and aid in the establishment of the P2P connections between two mobile applications. The modified version of the system is herein called Bitpoints, and the currency is instead constituted by points. The implemented loyalty card system benefits of some of the advantages of the popular cryptographic currency, namely the public access to the ledger for isolated verification of all transactions. The loyalty card permits the exchange of points between users and mining new points, which is fundamentally different than currently available loyalty cards. Within the context of this masters programme, a survey was delivery to a population constituted of 34 individuals, who answered a set of questions concerning the handling of the aforementioned prototype. The analysis of the obtained results allows to induce that people would feel comfortable with this application and accept the concept on which is based on, probably preferring a system similar to the proposed one.